Role of ultrasonography in the diagnosis of acute appendicitis in emergency cases - Ahmad, Syed Sajad; Gulzar, Asma; Amin, Huda (International Journal of Research in Medical Sciences, 2025)
Background: Acute appendicitis remains one of the most common surgical emergencies worldwide, demanding prompt and accurate diagnosis to prevent complications such as perforation or peritonitis. While computed tomography (CT) offers high diagnostic accuracy, ultrasonography (USG) serves as a safer, more accessible alternative, particularly in emergency and resource-limited settings. This study aimed to evaluate the diagnostic accuracy of ultrasonography in acute appendicitis by correlating USG findings with histopathological results among patients presenting with suspected appendicitis in the emergency department. Methods: A prospective observational study was conducted on 54 patients aged 8–60 years with clinical suspicion of acute appendicitis. All patients underwent graded compression ultrasonography using high-frequency linear and convex probes. Diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated using histopathological findings as the gold standard. Results: The appendix was visualized in 79.6% of patients. USG diagnosed appendicitis in 41 of 43 positive scans, with 2 false positives and 4 false negatives. The overall diagnostic performance of USG was sensitivity 91.1%, specificity 77.8%, PPV 95.3%, NPV 63.6%, and accuracy 88.9%. Common sonographic findings included a non-compressible tubular structure >6 mm (75.9%), periappendiceal fat stranding (64.8%), and Doppler hyperemia (51.9%). Accuracy was higher in non-obese patients (92.3%) compared to obese individuals (81.8%), and pediatric cases showed superior sensitivity (95%). Conclusions: Ultrasonography is a reliable, non-invasive, and efficient first-line imaging modality for diagnosing acute appendicitis in emergency settings. It demonstrates high sensitivity and accuracy comparable to CT when performed by skilled radiologists. Incorporating Doppler assessment and adopting a staged USG-CT approach in equivocal cases can further enhance diagnostic confidence while minimizing unnecessary radiation exposure.